Build back better what ss it, and what should it be?. - Noy, Ilan (Economics working papers., 2019)
This paper examines the economic dimensions of building back better (BBB) after disaster events and proposes four criteria for effectiveness: safety, speed, inclusiveness, and long-term economic potential. It aims to support planning by defining economic BBB more precisely and concretely, and suggests that these criteria provide a rough checklist. Neglecting any of them would make it much more difficult to meet the aim of building strong and resilient communities that are better able to cope with and bounce back from future disasters associated with natural hazards.